Pendampingan Personal Branding melalui Media Sosial guna Meningkatkan Potensi Lokal di Desa Nambangrejo Sukorejo Ponorogo - Fikri, Muhammad Khoirul; Fathoni, Tamrin; Sari, Dewi Yunita (Social Science Academic, 2024)
Nambangrejo Village has unique village assets, which can be categorized into several categories: tradition, art, traditional knowledge and culture. These assets of Nambangrejo Village are unique and different from other areas. Such as Mirah Hamlet and Golan Hamlet, which until now are still thick with traditions of not being allowed to marry between the two, even just meeting, this folklore is still believed until now. In terms of culture, Nambangrejo also has Reog Art, which is also a village asset. In terms of micro-economy, Nambangrejo also has umkm processed products whose resources can still be developed further. While from the religious sector, Nambangrejo Village also has Banjari art. Therefore, this service was carried out with the intention of identifying the potential of Nambangrejo Village using the Asset Basse Community Drive Development “ABCD” method to maximize local potential, especially Nambangrejo Village with the aim of sustainable potential development. Departing from such village assets, group 03 formulated the activity “Personal Branding Assistance Through Social Media to Increase Local Potential in Nambangrejo Village” by applying the ABCD method. The output of this research is to produce human resources (HR) of the Nambangrejo community who have knowledge and personal branding to project Nambangrejo Village sustainably.